Clinical drug resistance linked to interconvertible phenotypic and functional states of tumor-propagating cells in multiple myeloma - Chaidos, A.; Barnes, C.P.; Cowan, G.; May, P.C.; Melo, V.; Hatjiharissi, E.; Papaioannou, M.; Harrington, H.; Doolittle, H.; Terpos, E.; Dimopoulos, M.; Abdalla, S.; et al. (Blood, 2013)
The phenotype and function of cells enriched in tumor-propagating activity and their relationship to the phenotypic architecture in multiple myeloma (MM) are controversial. Here, in a cohort of 30 patients, we show that MM composes 4 hierarchically organized, clonally related subpopulations, which, although phenotypically distinct, share the same oncogenic chromosomal abnormalities as well as immunoglobulin heavy chain complementarity region 3 area sequence. Assessed in xenograft assays, myeloma-propagating activity is the exclusive property of a population characterized by its ability for bidirectional transition between the dominant CD19-CD138+ plasma cell (PC) and a low frequency CD19-CD138- subpopulation (termed Pre-PC); in addition, Pre-PCs are more quiescent and unlike PCs, are primarily localized at extramedullary sites. As shown by gene expression profiling, compared with PCs, Pre-PCs are enriched in epigenetic regulators, suggesting that epigenetic plasticity underpins the phenotypic diversification of myeloma-propagating cells. Prospective assessment in paired, pretreatment, and posttreatment bone marrow samples shows that Pre-PCs are up to 300-fold more drug-resistant than PCs. Thus, clinical drug resistance in MM is linked to reversible, bidirectional phenotypic transition of myeloma-propagating cells. These novel biologic insights have important clinical implications in relation to assessment of minimal residual disease and development of alternative therapeutic strategies in MM. © 2013 by The American Society of Hematology.